Analisis Pelaksanaan Program Aplikasi Kepul (Jual Beli Sampah) dalam Upaya Meningkatkan Kesadaran Masyarakat terhadap Kesehatan Lingkungan Helvetia Kecamatan Sunggal Kabupaten Deli Serdang - Nanda, Meutia; Deviyanti, Dira; Ramadan, Novrizal; Nurhamidah, Nurhamidah; Nasution, Finka Huzairi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The garbage problem is caused by several factors, one of which is the low awareness and concern of the community towards garbage. The Kepul application is a new breakthrough and innovation that serves as a platform to encourage the community to be more concerned about the health and cleanliness of the environment through the optimization of buying and selling recyclable waste through the Kepul application. The purpose of this research is to determine the success of the Kepul application program in increasing public awareness of environmental health. The method used in this research is a qualitative approach with descriptive methods and a case study research design, as well as data collection techniques including in-depth interviews, observation, and documentation. The research results obtained show the realization of environmental cleanliness and health and the ability to increase public awareness through the Kepul application program, and can change the community's mindset towards waste. It can be concluded that the Kepul implementation team has successfully encouraged the community to be more concerned about environmental health and cleanliness through the Kepul application in an effort to increase public awareness of environmental health.